Outcomes of Tibialis Anterior Tendon Reconstruction with Autograft or Allograft. (January 2022) - Andronic, Octavian; Unterfrauner, Ines; Jud, Lukas; Fritz, Benjamin; Viehöfer, Arnd F.; Fröhlich, Stefan; Imhoff, Florian B.; Wirth, Stephan H.
Background: In cases of tibialis anterior tendon (TAT) ruptures associated with significant tendon defect, an interposition graft is often needed for reconstruction. Both auto- and allograft reconstructions have been described in the literature. Our hypothesis was that both graft types would have a good integrity and provide comparable outcomes. Methods: Patients who underwent TAT reconstruction using either an auto- or allograft were identified. Patient-reported outcomes (PROs) were collected using the 12-Item Short Form Health Survey (SF-12) questionnaire, the American Orthopaedic Foot & Ankle Society (AOFAS) hindfoot score, the Foot Function Index (FFI), and the Karlsson-Peterson score. Functional outcome was assessed by isokinetic strength measurement. Outcomes were further assessed with magnetic resonance imaging (MRI) evaluation of graft integrity. All measurements were also performed for the contralateral foot. Results: Twenty-one patients with an average follow-up of 82 months (20-262 months), comprising 12 allograft and 9 autograft TAT reconstructions, were recruited. There were no significant differences in patient-reported outcomes between allograft reconstructions and autografts: SF-12 (30.7 vs 31.1, P = .77); AOFAS (83 vs 91.2, P = .19); FFI (20.7% vs 9.5%, P = .22); and Karlsson-Peterson (78.9 vs 87.1, P = .23). All grafts (100%) were intact on MRI with a well-preserved integrity and no signs of new rupture. There were no major differences in range of motion and functional outcomes as measured by strength testing between the operative and nonoperative side. Conclusion: Reconstructions of TAT achieved good PROs, as well as functional and imaging results with a preserved graft integrity in all cases. There were no substantial differences between allograft and autograft reconstructions. Level of Evidence: Level IV, retrospective case series.